Educational inequalities and decomposition of the urban-rural disparities in maternal health care utilization in Ethiopia: further analysis of 2019 intermediate Ethiopian demography and health survey - Mastewal Arefaynie; Anissa Mohammed; Abiyu Abadi Tareke; Awoke Keleb; Natnael Kebede; Yawkal Tsega; Abel Endawkie; Shimels Derso Kebede; Kaleab Mesfin Abera; Eyob Tilahun Abeje; Ermias Bekele Enyew; Chala Daba; et al. (BMC Public Health)
Abstract Introduction The utilization of maternal health services is vital to prevent maternal and child health problems. However, there is limited evidence as to why rural women have lower utilization and educational inequality in maternal health services utilization in Ethiopia. Identifying the causes is the first step to achieving maternal and child health initiatives. Objective The objective of this study was to decompose the urban-rural disparities and educational inequalities in maternal health care utilization in Ethiopia. Methods The study used the 2019 Ethiopian Demography Health Survey. Blinder-Oaxaca decomposition and multivariate decomposition analyses were done on a weighted 3,926.7 women to see the urban-rural differences in maternal health service utilization by using Stata 17.0. For the educational inequality of maternal health service utilization, concentration curve and concentration index were used by using conindex. P value < 0.005 was used to declare association. Result 84.89% of urban and 70.75% of rural residents use antenatal care and 73% of urban and 44% rural use institutional delivery. There was no urban-rural difference in postnatal care utilization. There was educational inequality in antenatal care (CIx 0.0926; p < 0.001), delivery care (CIx 0.2137; p < 0.001 and postnatal care (CIx 0.1272; p < 0.001) utilization in Ethiopia. 83.3% of antenatal care urban-rural difference was explained by women’s characteristics difference. Secondary (16.51%) and higher (23.01%) educational level difference of urban and rural women widening antenatal care utilization. Living regions (-1.33%) difference of urban and rural women mitigated antenatal care utilization. About 76.07% of the urban-rural difference in institutional delivery was explained by differences in the characteristics of women. Attending primary (3.76%), secondary (11.83%), and higher (8.44%) education, antenatal care (15.81%) difference of urban and rural women were widening institutional delivery utilization. Conclusion The urban-rural disparity in antenatal care and delivery care utilization is significant in the country. There were educational inequalities in maternal health service utilization. Attending, Secondary, higher, educational levels widening antenatal care and institutional delivery care utilization. Living regions mitigated antenatal care utilization. Antenatal care utilization widening institutional delivery utilization. Special attention is needed for rural women to improve maternal health service utilization through health extension workers and the women’s developmental army.